Values and ethics in organization and human systems development - Gellermann, William; Frankel, Mark S.; Ladenson, Robert F. (San Francisco : Jossey-Bass Publishers, 1990)
Values and ethics in organization and human systems development seeks to help OD-HSD professionals become more aware of and more insightful about ethical issues in their work.
Confronting professional values and ethical issues -- Developing a statement of values and ethics -- Cases and commentaries
Includes bibliographical references and index.
Keywords: ORGANIZATIONAL CHANGE -- MORAL AND ETHICAL ASPECTS; PERSONNEL MANAGEMENT